A user-choice model for locating congested fast charging stations. (February 2018) - Yang, Woosuk
Highlights: We derive a restriction for managing congestion at FCSs in a stochastic environment. We model a user-choice behaviour that EV users determine where to charge their EVs. We formulate a user-choice model fully reflecting the modelled behaviour. We also formulate several system-choice models partially reflecting it. A real-life case study is conducted to draw managerial implications from the models. Abstract: We consider a maximal coverage problem for locating congested fast charging stations and deploying chargers in a stochastic environment. A user-choice behaviour considering various factors is modelled. A user-choice model fully reflecting it and system-choice models partially reflecting it are derived. A case study shows the decisions by the system-choice models may result in huge congestion from the user-choice behaviour, and it gives the following main managerial implications for the user-choice model. The model seems to make robust location decisions for different settings of budget and utility function parameters, and it may give less coverage when allowing a long detour.